The Complementarily Indices of the Inland Freight Flows in the Nigerian Towns from Port Harcourt and Calabar Ports using Gravity Model (Global Journal of Science Frontier Research, 2018)
This paper is designed to examine the cargo traffic from Nigerian seaports, using the Calabar and Port Harcourt port complexes as the case study. The objective is to identify the function variables for assessing cargo flows from the seaport above to different towns in the country. A model depicting the functional relationship existing between the variables was used in the study. The regression model was used to fit a gravity model. It was discovered that population of towns is an important factor that affects cargo flows from Nigerian Sea Ports, while distance is a less predictive factor. Although the distance variable in this work was found to be insignificant as it has an inverse relationship with cargo volume, it does not connote that distance is not relevant in every flow study.
Keywords: flows; hinterland; freight; inland; and seaport